(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This paper analyzes the conflict between (1) the Right to respect for private and family life and (2) Freedom of thought, conscience and religion [articles 8 and 9 of European Convention on Human Rights (ECHR)] in the case Dulgheriu v. The London Borough of Ealing. In the first section, we make a brief description of the case. In the second section, we show the arguments used by the Court to rule this situation. In the third section, we verify the compatibility of the U.K. Court of Appeal’s decision with the ethical and juridical precepts. In the end, we concluded that autonomy has a public sphere that has to be respected. For this, the deductive and investigative methods will be used.